ANALISIS PENGARUH INJEKSI CO2 TERHADAP RECOVERY FACTOR MENGGUNAKAN SIMULASI CMG DI LAPANGAN X - Vera Fernanda; Mulia Ginting; Prayang Sunny Yulia (PETRO:Jurnal Ilmiah Teknik Perminyakan, 2019)
X-Field is located in South Sumatra, where there are several gas fields with considerable CO2 gas potential. In this field, no research has been conducted on CO2 injection neither in the laboratory nor simulation. Therefore, the purpose of this study is to analyze the effect of CO2 injection on the value of recovery factor with one-dimensional simulation using CMG. To be able to make an accurate simulation model, it is necessary to do validation by comparing the results obtained with the CO2 injection test from experiments in the laboratory. Laboratory experimental data used in this study is from Vulin’s literature. The result of recovery factor for X-field is 98.80%. From the results of this study, it is known that the injection rate of CO2 has no effect on changes in recovery factor. However, the difference of CO2 injection pressure in these two samples influences the change in recovery factor. The higher injection pressure of CO2 in an immiscible condition is, the higher the value of the recovery factor is achieved. In addition, the difference in oil composition in these two samples affects the value of MMP, where the higher the intermediate component of a reservoir fluid is, the lower the MMP will be. X-field has a high intermediate component fraction, therefore the value of MMP obtained is lower than the MMP from Vulin’s literature. The value of MMP in X-field is 2610.68 psia